Semantic Keyword-based Search on Structured Data Sources First COST Action IC1302 International KEYSTONE Conference, IKC 2015, Coimbra, Portugal, September 8-9, 2015. Revised Selected Papers - Cardoso, Jorge; Guerra, Francesco; Houben, Geert-Jan; Pinto, Alexandre Miguel; Velegrakis, Yannis (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the First COST Action IC1302 International KEYSTONE Conference on semantic Keyword-based Search on Structured Data Sources, IKC 2015, held in Coimbra, Portugal, in September 2015. The 13 revised full papers, 3 revised short papers, and 2 invited papers were carefully reviewed and selected from 22 initial submissions. The paper topics cover techniques for keyword search, semantic data management, social Web and social media, information retrieval, benchmarking for search on big data.